Small nucleoli are a cellular hallmark of longevity - Varnesh Tiku (Nature Portfolio, 2017)
Animal lifespan is plastic and is regulated by conserved signalling pathways. Here, Tikuet al.show that longevity-enhancing mutations or interventions are associated with reduced nucleolar size in worms, flies, mice and humans, and that nucleolar size can predict life-expectancy in individual worms.